Expression of Follicle-Stimulating Hormone Receptor in Von Hippel-Lindau Associated Tumors and Cysts: An Immunohistochemical Study (Journal of Kidney Cancer, 2025)
Von Hippel-Lindau (VHL) disease is a hereditary condition caused by mutations in the VHL-tumor suppressor gene leading to constitutive overproduction of HIF-1alpha and HIF-2alpha, two proangiogenic factors, involved in the development of highly vascular tumors. Published evidence has shown that FSH-receptor is expressed in endothelial cells of blood vessels (BV) in several types of tumors. Given that VHL-associated tumors are highly vascular, it is plausible that FSH-receptor could be expressed in their vasculature as well. This immunohistochemical study involved 71 patients diagnosed with VHL-associated tumors, who required surgical intervention. Tissue specimens from these patients included CNS-hemangioblastoma, pancreatic neuroendocrine tumors (panNET), and clear cell renal cell carcinoma (ccRCC). Immunohistochemical staining was performed using a highly specific monoclonal antibody against the human FSH-receptor to assess its expression in the endothelial cells and tumor cells. The distribution of FSH-receptor staining was analyzed using digital imaging techniques. FSHR-protein expression was detected in the BV endothelial cells in 100% of VHL-associated CNS-hemangioblastoma, panNET, and ccRCC cases. In CNS-hemangioblastoma, 96% of cases showed FSH-receptor positivity in tumor stromal cells. In panNET, 88% of the cases displayed FSH-receptor expression in tumor cells. No tumor cells showed FSH-receptor expression in ccRCC. This is the first study to demonstrate FSH-receptor expression by cells of VHL-associated tumors, with distinct expression patterns in different tumor types.